أثر تطبيق إدارة المعرفة على الأداء المؤسسي: دراسة تطبيقية على صندوق الضمان الاجتماعي بمدينة بنغازي - العبار، بشير محمد (جامعة سرت - كلية الاقتصاد, 2020)
هدفت الدراسة إلى التعرف على أثر تطبيق إدارة المعرفة وأبعادها (اكتساب المعرفة، توثيق المعرفة، نقل المعرفة، تطبيق المعرفة) على الأداء الأداء المؤسسي في صندوق الضمان الاجتماعي بمدينة بنغازي، ولتحقيق أهداف الدراسة، أتبع الباحثان المنهج الوصفي التحليلي، واستخدما أستماره الاستبيان كأداة رئيسية في تجميع البيانات، وقد تكون مجتمع الدراسة من جميع مديري الإدارات العليا والوسطى والتنفيذية والبالغ عددهم (110) مديرا، قام الباحثان بدراسته بالكامل باستخدام أسلوب الحصر الشامل، كما أستخدم برنامج الحزم الإحصائية (spps) في تحليل البيانات، وتوصلت الدراسة إلى العديد من النتائج، أهمها: إن مستوى تطبيق إدارة المعرفة ودرجة الأداء المؤسسي قد كانا مرتفعين، وكذلك وجود أثر ذو دلاله إحصائية لإدارة المعرفة بأبعادها مجتمعة على الأداء المؤسسي، ووجود اثر ذو دلاله إحصائية لكل بعد من أبعاد إدارة المعرفة (اكتساب المعرفة، توثيق المعرفة، نقل المعرفة، تطبيق المعرفة) على الأداء المؤسسي، وقد قدمت الدراسة مجموعة من التوصيات التي تسهم بتعزيز دور إدارة المعرفة في تحسين الأداء المؤسسي في صندوق الضمان الاجتماعي بمدينة بنغازي.
The study aimed to identify the impact of the application of knowledge management and its dimensions (knowledge acquisition, documenting knowledge, knowledge transfer, application of knowledge) on the institutional performance in the Social Security Fund in Benghazi. To achieve the objectives of the study, the researchers followed the descriptive and analytical method, and used the questionnaire form as the main tool in data collection. The study population consisted of all 110 senior, middle and executive directors. Through their full study, the researchers used a comprehensive inventory method, and the statistical packages for Social Sciences (SPSS) in the data analysis process. The study reached many results, the most important of which are: The level of knowledge management and the degree of institutional performance has been high. As well as the presence of a statistically significant impact of knowledge management with its combined dimensions on the institutional performance. In addition, there is a statistically significant impact of each dimension of knowledge management (knowledge acquisition, documenting knowledge, knowledge transfer, application of knowledge) on organizational performance. The study presented a set of recommendations that contribute to enhancing the role of knowledge management in improving the institutional performance of the Social Security Fund in Benghazi.
Keywords: إدارة المعرفة -- التأمينات الاجتماعية -- الضمان الاجتماعي -- بنغازي، ليبيا